Management of Teacher Professionalism Development: A Multi-Site Study of State Madrasah Aliyah in Langkat Regency - Ahmad Fuadi; Wahyudin Nur Nasution; Candra Wijaya (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to analyze the management of teacher professional development at Madrasah Aliyah Negeri throughout Langkat Regency. This study used a multi-site qualitative method where data collection techniques used interviews, observation, and documentation. The results of this study indicate that: 1) Management of Teacher Professionalism Development in State Madrasah Aliyah throughout Langkat Regency is directed at efforts to develop teacher professionalism in the form of increasing expertise, and skills, broadening horizons, coaching carried out on the initiative and in collaboration with the regional government and the District Ministry of Religion. Langkat through planning, implementing, supervising, and evaluating activities contained in various forms of activities, including K-13 socialization training and the covid curriculum, computer training, MGMP, supervision, making efforts for teachers to attend seminars, workshops, also seeking to add to the collection of books -books in the library.